The Effect of Teamwork, Internal Work Environment and Financial Compensation on Employee Performance at Sold Out Distro - Nadia Rahma Ayu Wijayanti; Dewi Andriani (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of Teamwork, Internal Work Environment and Financial Compensation on Employee Performance at Sold Out Distro in Tulangan Sidoarjo. The method used in this research is a quantitative approach method. Sampling in this study was carried out by non probability sampling method with saturated sample technique with the number of respondents as many as 95 respondents who become employees at Sold Out Distro in Tulangan Sidoarjo. Data collection techniques using a questionnaire. The data analysis technique used in this study uses multiple linear regression using the SPSS statistics version 25 program. The results of this study prove that Teamwork partially affect Employee Performance, Internal Work Environment partially affect Employee Performance and Financial Compensation partially affect Employee Performance.